Valuation of Contractual Health Transportation Company - Petrikovič, Jan (2012)
The purpose of my diploma thesis is to estimate objectivised value of contractual health transportation company. I am defining the value to the date 1st of January 2012. The gist of objectivised value is that the company follows its recent concept of business behavior, with the same management thinking. The value of the company is achieved by DCF valuation methods. Thesis is divided into several parts. The main parts are financial analysis and its output about the health of the company. Financial analysis is followed by strategic analysis that contains information about relevant markets and income forecasts. Next part is analysis and projection of generators of value. On the information from generators of value is based financial plan, which makes the last element for final valuation. Last part is the valuation itself.